Closing in on the Reservoir: Proactive Case Detection in High-Risk Groups as a Strategy to Detect Plasmodium falciparum Asymptomatic Carriers in Cambodia. (18th January 2018) - Rossi, Gabriele; Vernaeve, Lieven; Van den Bergh, Rafael; Nguon, Chea; Debackere, Mark; Abello Peiri, Carme; Van, Vuthea; Khim, Nimol; Kim, Saorin; Eam, Rotha; Ken, Malen; Khean, Chanra; et al.
Abstract : The article examines how to improve the detection of falciparum malaria asymptomatic carries within the frame of a polymerase chain reaction–based proactive case detection strategy in a preelimination setting in Cambodia, by mobilizing high-risk groups through specific health promotion messages. Abstract: Background: In the frame of elimination strategies of Plasmodium falciparum ( Pf ), active case detection has been recommended as complementary approach to the existing passive case detection programs. We trialed a polymerase chain reaction (PCR)–based active detection strategy targeting asymptomatic individuals, named proactive case detection (PACD), with the aim of assessing its feasibility, the extra yield of Pf infections, and the at-risk population for Pf carriage status. Methods: A pilot of PACD was conducted in 3 villages in Chey Saen district (Preah Vihear province, Cambodia), from December 2015 to March 2016. Voluntary screening and treatment, following health promotion sensitization, was used as mobilization strategy. Results: A total of 2802 persons were tested, representing 54% of the population. PACD (n = 30) and the respective reactive case detection (RACD) (n = 3) identified 33 Pf carriers, approximately twice as many as the Pf infections (n = 17) diagnosed in passive case detection and respective RACD, by health centers and village malaria workers using PCR, in the same villages/period. Final positivity rate was 1.07% (30/2802). People spending nighttime in forests and plantations were found to be at increased risk for Pf infection (odds ratio [OR], 3.4 [95% CI, 1.6–7.2], P = .002 and OR, 2.3 [95% CI, 1.1–4.9], P = .03, respectively). Conclusions: We demonstrated the usefulness of the PACD component in identifying Pf asymptomatic carriers. Social mobilization and promotion led to good attendance of specific risk groups, identified to be, in the Cambodian context, individuals spending nighttime in forest and plantations.